An α/β-Type, Small, Acid-Soluble Spore Protein Which Has Very High Affinity for DNA Prevents Outgrowth of Bacillus subtilis Spores - Hayes, Christopher S. (American Society for Microbiology, 2001)
A derivative of SspC, a minor α/β-type, small, acid-soluble spore protein (SASP) from Bacillus subtilis, was generated that has a very high affinity for DNA. This protein (SspC(Δ11-D13K)) was able to confer UV resistance on spores lacking α/β-type SASP, and spores with SspC(Δ11-D13K) triggered germination normally. However, SspC(Δ11-D13K) blocked outgrowth of ≥90% of germinated spores, and SspC(Δ11-D13K) persisted in these germinated spores, whereas wild-type SspC was almost completely degraded. The outgrowth phenotype of spores with SspC(Δ11-D13K) is proposed to be due to the high stability of the SspC(Δ11-D13K)-DNA complex, which prevents rapid degradation of this α/β-type SASP early in germination. The persistence of this protein on spore DNA then interferes with transcription during spore outgrowth.